Diversity of lichens and allied fungi on Norway spruce (Picea abies) in the middle boreal forests of Republic of Karelia (Russia) - Androsova, Vera I.; Tarasova, Viktoria N.; Gorshkov, Vadim V. (Folia Cryptogamica Estonica, 2018)
A detailed study of lichen diversity and estimation of epiphytic lichen cover characteristics on spruce as a key ecosystem component was performed in boreal forests of Karelia (NW Russia). The aims of the present paper are: (1) to study lichen diversity on Norway spruce in the middle boreal forests of southern Karelia (NW Russia), and (2) to estimate the main characteristics of epiphytic lichen cover on spruce trunks and branches. In total, 158 species of lichens and allied fungi were found on spruce, including 108 species on trunks, 78 on branches and 55 on snags. Seventeen species are listed in the Red Data Book of Republic of Karelia. Ten species are new for the biogeographical province Karelia transonegensis and two for the province Karelia onegensis. Twenty-two species are considered old-growth forest indicators. The total epiphytic lichen cover on spruce trees averaged 59% at the trunk base, 12% at a height of 1.3 m above ground level and 61% on branches. Predominantly, only 12 species contributed to the lichen cover of trunk and branches. Despite the predominance of crustose lichens colonising spruce trees, the main epiphytic lichen cover both on trunks and branches was provided largely by foliose species (57% of the total cover). Due to a variety of morphological features, spruce provides diverse microhabitats, which leads to high lichen species richness with different ecological requirements. Spruce trees play a significant role in maintaining the diversity and conservation of rare species.